The second sister : a novel - Kendal, Claire (Harper, an imprint of HarperCollinsPublishers, 2017)
A decade after the disappearance of her older sister, Miranda, Ella Brooke's obsessive quest to solve the mystery brings her into contact with Jason Thorne, a serial killer locked away in a psychiatric institution.